Infective pneumonia following the use of tumor necrosis factor-α inhibitors in inflammatory bowel disease patients: A real-world disproportionality analysis of the FDA Adverse Event Reporting System (FAERS) database - Qinhui Tang; Xiaowei Tang; Wenmeng Yin; Yantong Li; Xiaolin Zhong (PLoS ONE, 2025)
Background Patients with inflammatory bowel disease may develop infective pneumonia after using tumor necrosis factor-α inhibitors(TNFis). Due to the limitations of clinical trials, the occurrence of infective pneumonia in patients with inflammatory bowel disease using tumor necrosis factor-α(TNF-α) inhibitors remains uncertain. This article primarily explores the relationship between TNF-α inhibitors and adverse events(AEs) related to infective pneumonia in the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. Methods We collected data from the FAERS database, extracting reports for each TNF-α inhibitor from their market launch until the first quarter of 2024 (infliximab, adalimumab, certolizumab pegol, and golimumab) and assessing infective pneumonia associated with TNF-α inhibitors using disproportionality analysis. Results After removing duplicate reports, a total of 7176 reports were included. Infliximab and adalimumab exhibited the highest incidence of infective pneumonia-related adverse events, occurring in 3,858 and 2,819 cases, respectively, whereas certolizumab pegol and golimumab showed lower incidences with only 297 and 202 cases. Infliximab had the most positive signals, totaling 10, including tuberculosis, pulmonary tuberculosis, pneumocystis jirovecii pneumonia, histoplasmosis, pneumonia bacterial, pneumonia legionella, bronchopulmonary aspergillosis, tuberculous pleurisy, pneumonia cryptococcal, blastomycosis. Golimumab had seven positive signals, including pneumonia, tuberculosis, pulmonary tuberculosis, bronchopulmonary aspergillosis, pneumonia legionella, pneumonia bacterial, and COVID-19 pneumonia. Certolizumab pegol had only two positive signals: pneumonia and pneumonia klebsiella. However, adalimumab did not show signals of infective pneumonia. Conclusion Except for adalimumab, the other three TNF-α inhibitors showed positive signals related to infective pneumonia, with tuberculosis-related diseases being the most common. Our study provides important insights for healthcare professionals, which can help reduce the occurrence of infective pneumonia associated with TNF-α inhibitors.